Development of Flash Card Media to Improve Beginning Reading Skills of Grade 1 Students at SDN 05 Pulau Punjung - Putri, Suci Rahma; Hasibuan, Rusdi Indra; Rahayu, Mustika (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the problems faced by students who have not yet memorized letters, struggle to distinguish similarly shaped letters, experience difficulties in spelling, and are not yet fluent in reading. The purpose of this study is to produce flash card media that is valid, practical, and effective. The type of research used is Research and Development (R&D), employing the PLOMP development model, which consists of three stages: preliminary research, prototyping phase, and assessment phase. The validity of the flash cards was assessed by four validators: the language expert validation scored 96.25% and was categorized as very valid; the material expert validation scored 96.25% (very valid); the media expert validation scored 95.31% (very valid); and the teaching module validation scored 98.7% (very valid). The practicality of the flash card media, based on a teacher response questionnaire for first-grade teachers, received a score of 100% and was categorized as very practical, while the student response questionnaire obtained an average score of 90.5%, also categorized as very practical. The effectiveness results based on learning tests of students at the primary school yielded an average of 94.73%, categorized as very effective. From the one-to-one evaluation trial, an average of 95.5% was obtained, categorized as very practical, and from the small group evaluation trial, an average of 95.6% was obtained, also categorized as very practical. The effectiveness data were analyzed based on students' learning outcomes.